Health and Human Rights: New challenges for social responsiveness - Leslie London; Marion Heap; Laurel Baldwin-Ragaven (Gateways, 2009)
South Africa’s struggle against apartheid discrimination, including struggles in the health sector, laid the basis for a vibrant engagement of staff and students in human rights research, teaching and outreach in the Health Sciences Faculty at the University of Cape Town (UCT). This article provides a brief overview of this background context, then shows how this engagement has continued with new challenges emerging in the post-apartheid democratic period. Teaching at undergraduate and postgraduate levels has been complemented by a programme of ‘Training the Trainers’ in health and human rights. The programme targets teachers of health professionals at institutions in South and Southern Africa, resulting in national adoption of human rights competencies as an essential component of health professionals’ skills base. Research has also extended lessons learnt from the apartheid period into work with vulnerable groups, such as rural farm workers and the deaf, and seeks to build the capacity of marginal populations to change the conditions of their vulnerability in order to realize their rights. Partnerships with civil society organisations have been a strong thread, creating new knowledge and new ways of joint work towards realizing the right to health, including advocacy engagement in civil society movements and regional networks. Further, a focus on health professionals’ practice, in terms of dealing with potential dual loyalty conflicts and their role as gatekeepers in the health services on matters of patients’ rights, has shaped the research agenda. This article illustrates how knowledge production for the public good extends beyond notions of enhancing economic productivity for national development and provides a base for transdisciplinary and transinstitutional engagement. Additionally, non-traditional forms of knowledge networking and transfer have also been explored, including engagement with policy-makers and health managers. Finally, it is shown how the portfolio of social responsiveness activities in the health and human rights envelope has offered significant and novel mutual benefits to the University and the community.